2014
DOI: 10.1016/j.meatsci.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mortadella formulated with carbon monoxide-treated porcine blood

Abstract: The proximate composition and color of mortadellas containing carbon monoxide-treated (COTB), untreated (UNTB), or CO-treated dried blood (CODB) were compared to that of control mortadella. Blood addition did not affect (P>0.05) the proximate composition and TBARS. The mortadella containing 10% UNTB were brown and those containing COTB or CODB were red. Residual nitrite level, L*, a*, b* and c* values of the mortadella decreased (P<0.05) with an increase in the amount of blood; TBARs did not vary (P>0.05). Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, addition of NaNO 2 resulted in a significant (p<0.05) increase in a* values in the presence of COHb, indicating that COHb and NaNO 2 had a synergistic influence on a* values. Similarly, COHb and NaNO 2 reportedly synergistically increased a* values of chicken sausage (2) and mortadella (7).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, addition of NaNO 2 resulted in a significant (p<0.05) increase in a* values in the presence of COHb, indicating that COHb and NaNO 2 had a synergistic influence on a* values. Similarly, COHb and NaNO 2 reportedly synergistically increased a* values of chicken sausage (2) and mortadella (7).…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, COHb or a combination of COHb and sodium nitrite (NaNO 2 ), is reported to improve the color and/or other physicochemical properties of pork sausage during storage (1,2). A similar phenomenon is also observed in mortadellas formulated with CO-treated porcine blood (7). Thus, COHb shows potential for use in meat product formulations.…”
Section: Introductionmentioning
confidence: 84%
“…Other researchers noted that addition of both COHb and NaNO2 synergistically increased the nitroso pigment contents and synergistically decreased residual nitrite contents (Xu et al, 2016). Pereira et al (2014) and Xu et al (2016) showed that COHb has potential for use in meat product formulations. The addition of blood treated with carbon monoxide allows the production of better-colored meat products having lower residual nitrite levels.…”
Section: Future Trendsmentioning
confidence: 98%
“…After glycosylation, the stability of nitrosohemoglobin will be improved [ 61 , 62 ]. Liquid or dry blood treated with carbon monoxide can also be used as colorants in meat products, which has been proved to be feasible in mortadella [ 63 , 64 ]. More importantly, tea polyphenols can also affect the stability and color of hemoglobin, which is connected with the concentration of tea polyphenols [ 65 ].…”
Section: Proteins In Meatmentioning
confidence: 99%